Pengaruh Brand Image dan Kemudahan Akses terhadap Minat Berqurban di Masjid dengan Moderasi Religiusitas - Amorita Azizah Alpha; Yudi Sutarso (Indonesian Journal of Islamic Economics and Business, 2023)
The condition of the majority Muslim population in Indonesia has a very significant potential for qurban (sacrifice). The development of community interest in qurban increases every year. This is because the organization of qurban slaughtering has become a routine for Muslim communities. Additionally, qurban also serves as a driving force for the economy and culture. The recommended location for qurban is the same as the place for Eid prayers, where mosques are one of the main choices for qurban. Factors influencing the community's interest in performing sacrifices in mosques are one of the aspects that need attention. Therefore, research is conducted to analyze these factors. However, it is not impossible for qurban to be performed elsewhere. This research involves 158 respondents from the Muslim community in Sidoarjo. Data is collected using Purposive Sampling and processed using SmartPLS. The data processing results indicate that brand image does not directly influence, but indirectly, with trust as a mediator, it has an effect on the interest in performing qurban in mosques. Direct and indirect ease of access, using trust as a mediator, has an effect on interest. Meanwhile, religiosity cannot moderate the relationship between brand image and ease of access to the interest in performing qurban in mosques.